Edge‐hydroxylated Boron Nitride for Oxidative Dehydrogenation of Propane to Propylene. Issue 10 (6th April 2017) - Shi, Lei; Wang, Dongqi; Song, Wei; Shao, Dan; Zhang, Wei‐Ping; Lu, An‐Hui
Abstract: Oxidative dehydrogenation of propane to olefins is a promising alternative route to industrialized direct dehydrogenation, but encounters the difficulty in selectivity control for olefins because of the overoxidation reactions that produce a substantial amount of undesired CO2 . Here we report edge‐hydroxylated boron nitride, a metal‐free catalyst, that efficiently catalyzed dehydrogenation of propane to propylene with superior selectivity (80.2 %) but with only negligible CO2 formation (0.5 %) at a given propane conversion of 20.6 %. Remarkable stability was evidenced by the operation of a 300 h test with steady conversion and product selectivity. The active BNO . site, generated dynamically through hydrogen abstraction of B−OH groups by molecular oxygen, triggered propane dehydrogenation by selectively breaking the C−H bond but simultaneously shut off the pathway of propylene overoxidation towards CO2 . Abstract : Olefin generation without a metal : Edge‐hydroxylated boron nitride shows superior selectivity for the oxidative dehydrogenation of propane to propylene with only negligible CO2 formation. The dynamically generated active BNO . site triggers propane dehydrogenation by selectively breaking the C−H bond by concomitantly avoiding propylene oxidation to CO2 .